Deteksi Cemaran Escherichia Coli Dan Staphylococcus Aureus pada Pangan Tradisional Ayam Betutu di Destinasi Wisata Pantai Seminyak Bali - Aritonang, Melda Sari; Darmayanti, Luh Putu Trisna; Sugitha, I Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2024)
Abstract Betutu chicken has the potential for microbiological contamination due to the presence of pathogenic microbes. Microbiological contamination comes from equipment or a less clean environment. The purpose of the study is to confirm the presence of microbial defilement in betutu chicken and hygiene measures implemented by restaurants in Seminyak Beach, Bali. Research conducted through surveys with sampling techniques using random sampling, displayed in a table format and is analyzed in explanatory. Parameters observed include the total number of microbes, coliforms, Escherichia coli , and Staphylococcus aureus . Based on the study, 100% of betutu chickens still meet the necessities for the full number of organisms (< 1 x 10 6 colonies/g), 100% contain coliforms, 50% do not meet the requirements for the amount of E.coli (< 1 x 10 2 colonies/g), and 100% meet the requirements for the number of S. aureus (< 2 x 10 2 colonies/g). Sanitation practices at restaurants that sell betutu chicken in Seminyak Beach include purchasing raw materials from the local market, direct processing of 50% of raw materials, processing 65% of betutu chicken in the morning, 37.5% of sellers using hygiene tools, and personal hygienic sanitation that still needs to be improved. Keywords : Chicken betutu , Total microbes, coliform , Escherichia coli , Staphylococcus aureu s.